Using sampling concepts, the population and the sample are given as follows:
d. population: 6,000 batches of 100 cards sample: every 100th batch.
<h3>What is sampling?</h3>
It is a common statistics practice, when we want to study something from a population, we find a sample of this population, which is a <u>group containing elements of a population</u>. A sample has to be representative of the population, that is, it has to involve all segments of the population.
For example:
I want to estimate the proportion of New York state residents who are Buffalo Bills fans. So I ask, lets say, 1000 randomly selected New York state residents whether they are Buffalo Bills fans, and then:
- The population is: All New York State residents.
- The sample is the 1000 randomly selected New York state residents.
Hence, in the situation described the population is the 6,000 batches of 100 cards, while the sample is every 100th batch, hence option d is correct.
More can be learned about sampling concepts at brainly.com/question/25122507
#SPJ1
probability = favourable outcomes/total outcomes
you need 1 banana, out of 4 and there are total of 6 items so probability will be 4/6
when you take out 1 banana, there are 3 banana left and total of 5 items
so probability of this action will be 3/5
now, next action is taking out another banana.
this is NOT an independent event.
so by we will multiply the probabilities of these events according to rule of products.
so the answer is
or 2×100/5=40%
x = 3 + y Eqn(1)
y = -2x + 9 Eqn(2)
Let us solve the system of equations with the substitution method
x - 3 = y (Subtracting 3 from both sides of the Eqn(1))
Replacing y = x - 3 in Eqn (2), we have:
x - 3 = -2x + 9
x = -2x + 9 + 3 (Adding 3 to both sides of the equation)
x + 2x = 9 + 3 (Adding 2x to both sides of the equation)
3x = 12 ( Adding like terms)
x = 12/3 (Dividing by 3 on both sides of the equation)
x = 4
Replacing x=4 in Eqn(1), we have:
4 = 3 + y
4 - 3 = y (Subtracting 3 from both sides of the equation)
y=1
The answers are:
x= 4 and y=1
Plug in -3 for x
f(-3) = 2(-3) - (-3 + 6)
f(-3) = -6 - (3)
f(-3) = -9
Solution: f(-3) = -9
Answer:
discrete i think i might be wrong
Step-by-step explanation: